ISOLATION AND CHARACTERIZATION OF POTENTIAL ENDOPHYTIC BACTERIA FROM RICE - S. TRIVENI and S.N.C.V.L. PUSHPAVALLI, C. SWATHI, BHARATI N. BHAT, G. UMA DEVI (The Journal of Research, PJTSAU, 2023)
Rice (Oryza sativa L.) is a key staple food for the world’s growing population and is widely cultivated in tropical and subtropical locations, where it is affected by many biotic diseases of which bacterial infections are also causing losses. Bacterial endophytes are known to confer tolerance or resistance to the host plant from various biotic and abiotic stresses. Endophytes influence the physiology and developmental processes of the host plant, by releasing antimicrobial metabolites, synthesising phytohormones, siderophore, competing with pathogens for space and nutrients, and modulating the plant resistance response. Because of the crop’s economic importance, endophytic bacteria have received a lot of attention as biocontrol agents and are the most common, most efficient, environmentally sustainable, and cost-effective. The serial dilution technique was used to isolate 52 endophytic bacterial isolates from rice roots, stems, and leaves. Colony characteristics were recorded after the isolates were purified. Rice varieties like BPT 5204, JGL, and KNM genotypes had significantly greater mean endophytic bacterial populations. By using the cross-streak method, all the isolates were tested for antagonistic activity against bacterial leaf blight. Disease inhibition zones were found in fifteen isolates. For these fifteen isolates, biochemical characterizations such as siderophore, HCN, IAA, catalase, citrate, oxidase, hydrogen sulphide, indole, voges prausker’s, casein, gelatin, pectinase, and cellulose tests were performed. IAA, HCN, Siderophore, Ammonia, Phosphate, Nitrogen, Potassium, and Zinc Solubilization were investigated as growth promoters. Four isolates were chosen for development of bacterial consortium as a biocontrol agent based on antagonistic, biochemical, growth promoting, and nutrient solubilization properties.